The heritage and landscapes: new concepts for old ideas? - Figueiredo, Vanessa Gayego Bello (2013)
This article investigates the relationship between landscape and heritage and brings a brief critical analysis of the United Nations Educational, Scientific and Cultural Organization (UNESCO) practice since the institutionalization of cultural landscape category, created on the World Heritage list in 1992, until 2012. The text is structured in three parts. The first presents a brief historical approach about the concept of Western landscape. The second presents recent formulations on the cultural landscape based on international conventions, such as the Council of Europe (1995) and the Landscape European Convention (2000). The third part focuses on the analysis of the World Heritage Committee work, comprising the main characteristics and values of cultural landscapes listed. Finally, the study reveals how the employment of this new concept is still reflecting old conceptions of landscape and preservation, although points towards perspective in the heritage policies, especially as regards the own expansion of the heritage concept and the approximation between the natural and cultural, material and immaterial dimensions.